Population structure and habitat of a tropical tree with edible fruits, Annona purpurea (Annonaceae), in Western Mexico - Topete-Corona, Citlally (2020)
Abstract. Introduction: Annona purpurea is a Mesoamerican tree, distributed from the Pacific and Atlantic slopes of Mexico to South America. Different parts of the plant are of utility and the fruits are edible. Objective: To describe the population structure, habitat and environmental factors that influence the distribution and abundance of A. purpurea in Western Mexico. Methods: From April to November 2015, 24 sampling units were established, each of which were 500 m2 in area and had a presence of A. purpurea. At each site, all woody species with a diameter at breast height (dap) ≥ 2.5 cm were measured and identified, and environmental, geographic and climatic information recorded. Information regarding the regeneration of the species was obtained. The structure of A. purpurea was estimated and its relationships with environmental variables examined. The Whittaker association index was determined using the importance value index matrix (IVI). With the matrix of environmental variables and that of IVI, a Canonical Correspondence Analysis was performed to determine the influence of environmental variables on the species and to visualize the distribution of the species in multidimensional space. Results: A. purpurea presented 1 108 stems in 1.2 ha, with 85 % of these concentrated in the first three diametric categories. Its density presented a positive relationship with the presence of stumps, while the basal area and IVI were similarly related to the incidence of fire. There was little or no regeneration of A. purpurea under its canopy. The highest IVI in the community were found for A. purpurea, Tabebuia rosea, Quercus magnoliifolia and Enterolobium cyclocarpum, and the similarity profiles test separated A. purpurea and Guazuma ulmifolia as a distinct group. The environmental variables with the greatest influence on the distribution and abundance of A. purpurea were annual precipitation, fire incidence, elevation, mean annual temperature, stoniness and livestock. Conclusion: A. purpurea presents the greatest structural attributes in the community, its populations are favored in places with greater precipitation and temperature, with little stoniness and with incidence of disturbances by fire and livestock that generate large gaps and its greatest association is with G. ulmifolia.